Bevacizumab and the risk of arterial and venous thromboembolism in patients with metastatic, castration‐resistant prostate cancer treated on Cancer and Leukemia Group B (CALGB) 90401 (Alliance). Issue 7 (21st November 2014) - Patel, Jai N.; Jiang, Chen; Hertz, Daniel L.; Mulkey, Flora A.; Owzar, Kouros; Halabi, Susan; Ratain, Mark J.; Friedman, Paula N.; Small, Eric J.; Carducci, Michael A.; Mahoney, John F.; Kelley, Michael J.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Bevacizumab is associated with an increased risk of arterial thromboembolism (ATE); however, its effect on venous thromboembolism (VTE) remains controversial. Scant data exist on the factors that increase the risk of ATE/VTE in patients with prostate cancer. The authors investigated the association of bevacizumab treatment and clinical factors with ATE/VTE risk in patients who were treated on Cancer and Leukemia Group B (CALGB) trial 90401. METHODS Patients with metastatic, castration‐resistant prostate cancer were randomized to receive docetaxel and prednisone with or without bevacizumab once every 21 days. Cycle‐to‐event Cox regression models were used to investigate the association of bevacizumab with the incidence of grade 3 or greater (≥3) ATE and VTE. Age, prior ATE/VTE, baseline antiplatelet/anticoagulant use, and VTE risk score (based on leukocyte count, hemoglobin, platelet count, body mass index, and tumor location) were evaluated in univariate and multivariable analyses. RESULTS Of 1008 randomized patients, the odds of experiencing grade ≥3 ATE were significantly greater in those who received bevacizumab compared with those who received placebo (odds ratio, 2.79; P = .02), whereas an opposite trend was noted for grade ≥3 VTE (odds ratio, 0.60; P = .08). In the multivariable analysis, bevacizumab treatment (hazard ratio [HR], 3.00; P = .01) and age (HR, 1.06; P = .02) were significantly associated with the risk of ATE; whereas age (HR, 1.05; P = .01) and VTE risk score (HR, 1.83; P = .03) were significantly associated with the risk of VTE. CONCLUSIONS Bevacizumab was significantly associated with a greater risk of ATE in patients with metastatic, castration‐resistant prostate cancer, but it was not significantly associated with the risk of VTE. Understanding clinical factors that increase the risk for experiencing ATE/VTE is essential to mitigate the risks and reduce the burden of these prevalent complications in cancer care. Cancer 2015;121:1025–1031. © 2014 American Cancer Society.